(3GdOhd GdfGejI hGdJLGQI GdYGdejI (B:s (3GdCOGA hGdCaGb GdeSJbHdjI (B/s - (3CcjhR, jdeGXs; (3GdSjO, CMeO YHO GdNGdbs ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 2006)
(3OjfGejcjI GdUGOQGJ hGdJUfjY aj GdOhd GdfGejI(B- (3GdefGaSI hGdhge GdeJYdb Hgjcd GdUGOQGJ(B- (3fXGe GdUjf Gdi efXeI GdJLGQI GdYGdejI(B- (3EOGQI GdEfOeGL hGdJUfjY(B.s
Keywords: (3GdJLGQI GdYGdejIs; (3GdOhd GdfGejIs